2016
DOI: 10.1016/j.jdiacomp.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Urine AQP5 is a potential novel biomarker of diabetic nephropathy

Abstract: Aims To investigate if urinary AQP5 serves as a new potential biomarker of diabetic nephropathy. Methods Using an AQP5-specific enzyme-linked immunosorbent assay, we measured serum and urine AQP5 first in a cohort consisting of normal controls (n = 26) and patients with diabetes mellitus (n = 25) or diabetic nephropathy (n = 33) and then in a validation cohort possessing normal controls (n = 10), patients with diabetes mellitus (n = 10) or diabetic nephropathy (n = 14), and patients with chronic kidney disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
11
10
1
Order By: Relevance
“…Our results about the upregulation of uAQP5 in DN patients are in line with previous findings from Wu et al [ 25 ] who reported that AQP5 was expressed in the collecting ducts of patients with DN. During the preparation of this manuscript, the same authors demonstrated, with a similar approach, that uAQP5 is upregulated in the urine of DN patients and positively correlated with the stage of DN [ 45 ]. In their study, however, they classified DN patients to stages III, IV, and V on the basis of microalbuminuria and macroalbuminuria and increased serum creatinine and limited their analysis to uAQP5 alone.…”
Section: Discussionmentioning
confidence: 99%
“…Our results about the upregulation of uAQP5 in DN patients are in line with previous findings from Wu et al [ 25 ] who reported that AQP5 was expressed in the collecting ducts of patients with DN. During the preparation of this manuscript, the same authors demonstrated, with a similar approach, that uAQP5 is upregulated in the urine of DN patients and positively correlated with the stage of DN [ 45 ]. In their study, however, they classified DN patients to stages III, IV, and V on the basis of microalbuminuria and macroalbuminuria and increased serum creatinine and limited their analysis to uAQP5 alone.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence showed that the expression of AQPs was dysregulated in DN patients. AQP5 is obviously increased in the kidney tissue of DN patients and urine AQP2 and AQP5 have been identified as potential novel biomarkers of diabetic nephropathy with sensitivity, early appearance, and low invasiveness features [68,69,70]. A community-based cohort study involving 620 participants with chronic kidney disease (CKD) firstly revealed that AQP11 rs2276415 variant is associated with CKD progression [69].…”
Section: Aqps In Diabetic Nephropathymentioning
confidence: 99%
“…First, the small size (27 kD) permits direct secretion of AQP5 into urine from tubular cells. Secondly, urinary AQP5 may result from a reduction in tubular reabsorption, given the correlation between urine and serum AQP5 levels 10 . The final likeliness of 11 high urine levels of AQP5 is the shedding of AQP5-expressing tubular cells, as evidenced by the detection of detached AQP5 + cells in the lumen of the tubules 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Baseline urine samples were stored at −80°C from the time of collection. Human AQP5 was measured using an AQP5-specific ELISA kit, as we previously reported 10 . For each patient, AQP5 was blindly measured in triplicates, averaged, and log2 transformed.…”
Section: Aqp5 Measurementsmentioning
confidence: 99%
See 1 more Smart Citation